Applications nature aware virtual machine provisioning in cloud. (2018) - Achar, Raghavendra; Thilagam, P. Santhi
Rapid growth of internet technologies and virtualisation has made cloud as a new IT delivery mechanism, which is gaining popularity from both industry and academia. Huge demand for a cloud resources, running similar nature applications in the same server results in application degradation whenever there is a sudden rise in workload. In order to minimise the application degradations, there is an urgent need to know the nature of applications running in cloud for efficient virtual machine (VM) provisioning. Existing cloud architecture does not provide any mechanism to handle this issue. This paper presents a modified cloud architecture which contains additional component called application analyser to identify the nature of applications running in each VM. Based on applications nature, this paper presents a novel VM provisioning mechanism using genetic algorithm. In order to utilise the resources efficiently, this paper also presents a mechanism for VM provisioning with migration. Experimental study is conducted using CloudSim simulator shows that proposed mechanism is efficiently allocating resources to the virtual machines.